Final answer:
To solve for h(r), you divide both sides of the given equation q - 10 = 6(r + 1) by 6(r + 1), resulting in the correct formula h(r) = (q - 10) / 6(r + 1). After dividing, you get h(r) = (q - 10) / 6(r + 1), which is option a).
Step-by-step explanation:
The question is asking to solve for h(r) given the equation q - 10 = 6(r + 1). To find h(r), you need to isolate it on one side of the equation. Therefore, you divide both sides of the original equation by 6(r + 1) to find h(r).
The correct formula is: h(r) = (q - 10) / 6(r + 1)
Here's the step-by-step explanation:
- Start with the given equation: q - 10 = 6(r + 1).
- To solve for h(r), you need to isolate h(r) which means getting h(r) by itself on one side of the equation.
- The term 6(r + 1) is multiplying h(r), so you divide both sides of the equation by 6(r + 1) to cancel it out on the right side.
- After dividing, you get h(r) = (q - 10) / 6(r + 1), which is option a).